Creep data sheet for Nickel-based 19Cr-18Fe-3Mo-5Nb-Ti-Al superalloy - Kota Sawada; Yasushi Taniuchi; Kaoru Sekido; Takehiro Nojima; Tomotaka Hatakeyama; Kazuhiro Kimura (Science and Technology of Advanced Materials: Methods)
Creep data of Ni-based 19Cr-18Fe-3Mo-5Nb-Ti-Al superalloy (JIS NCF718-B) were obtained at 550°C to 750°C under 100MPa to 1000MPa and analyzed to determine the 100,000 h creep rupture strength. The tensile properties were also evaluated at room temperature to 750°C. Four heats of JIS NCF718-B were used in this study. There was no large difference in the 0.2% proof stress and tensile strength among the heats. A difference in the tensile ductility was observed at 650°C to 750°C among the heats. Heat-to-heat variation of the creep rupture strength was confirmed among the heats and the variation became large in the long term. Regression analysis was conducted for the tensile test data of the four heats. The creep rupture data of all the heats were fitted to the regression equation of logarithmic stress using the time – temperature parameters of Larson – Miller, Orr – Sherby – Dorn, and Manson – Haferd to estimate the 100,000 h creep rupture strength. The Orr – Sherby – Dorn parameter and regression equation of the second degree was suitable for the creep strength evaluation.